"Together Make a Visit; Together Make a Plan": Messaging to Adult Children with Concerns about a Parent's Memory Loss. Issue 4 (20th March 2020) - Jordan, Amy; Bleakley, Amy; Harkins, Kristin; Hailu, Tigist; Cassidy, Kyle; Hachey, Sara; Karlawish, Jason
ABSTRACT: Using the integrative model (IM), we developed and tested messages to encourage adults to accompany their parent to a memory doctor for a cognitive evaluation. We conducted in-depth interviews ( n = 60) with African American and White adults with a parent age 65+ to identify key beliefs. Next, we carried out an IM-based telephone survey with a representative sample of the target population ( n = 541). Analyses revealed that attitudes varied depending on the gender of the parent. Resulting messages featuring mothers countered the fear of hearing bad news and the belief that mother does not want to be accompanied to the doctor's office. Messages featuring fathers highlighted the belief that attending a doctor's visit will provide father emotional support. We subsequently tested messages with focus group participants ( n = 48) and refined them. This study advances our understanding of opportunities to communicate about memory loss, including Alzheimer's disease and dementia, in ways that encourage a behavioral action that will benefit older adults and their families.